PENINGKATAN MOTIVASI SISWA DALAM MEMATUHI PERATURAN TATA TERTIB SEKOLAH MELALUI KONSELING INDIVIDU SMAN 2 TANJUNG SELOR - SYAHRIANI MUHAIJANG (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2022)
This research is an action research on counseling guidance which aims to increase the motivation of class X IPS students at SMA Negeri 2 Tanjung Selor in complying with school rules and regulations through individual counseling. This research was conducted for 2 cycles. The collected data were analyzed using qualitative analysis and quantitative analysis. Based on the results of data analysis on the motivation of students in complying with the disciplinary rules in cycle 1, a score of 44 violations was obtained, meaning that the motivation of students in complying with the disciplinary rules was good. In cycle 2, a score of 7 violations was obtained, meaning that the motivation of students in complying with school rules and regulations was very good. In addition, data was obtained from the observation sheet that students had come and left school according to schedule, students had worn complete and neat uniforms according to school rules, students had carried out picket duties, students stayed away from school restrictions, for example, smoking was not permitted. , may not wear excessive make-up. By using individual counseling the motivation of students is very high in complying with the rules of conduct so that there are no more students who violate the rules of order and are more disciplined. ABSTRAKPenelitian ini adalah penelitian tindakan bimbingan konseling yang bertujuan untuk meningkatkan motivasi peserta didik kelas X IPS SMA Negeri 2 Tanjung Selor dalam mematuhi peraturan tata tertib sekolah melalui konseling individu. Penelitian ini dilaksanakan selama 2 siklus. Data yang terkumpul dianalisis dengan menggunakan analisis kualitatif dan analisis kuantitatif. Berdasarkan hasil analisis data tentang motivasi peserta didik dalam mematuhi peraturan tata tertib pada siklus 1 di peroleh skor jumlah pelanggaran 44 artinya motivasi peserta didik dalam mematuhi peraturan tata tertib sekolah sudah baik. Pada siklus 2 diperoleh skor jumlah pelanggaran 7 artinya motivasi peserta didik dalam mematuhi peraturan tata tertib sekolah sangat baik. Selain itu di peroleh data dari lembaran observasi bahwa peserta didik sudah datang dan pulang sekolah sesuai jadwal, peserta didik sudah memakai seragam yang lengkap dan rapi sesuai aturan sekolah, peserta didik sudah melaksanakan tugas piket, peserta didik menjauhi larangan-larangan sekolah misalnya tidak boleh merokok, tidak boleh memakai make up yang berlebihan. Dengan menggunakan konseling individu motivasi peserta didik sangat tinggi dalam mematuhi peraturan tata tertib sehingga tidak ada lagi peserta didik yang melanggar peraturan tata tertib dan lebih disiplin.